Implementasi Pengembangan Materi Ajar Interferensi Leksikon Bahasa Inggris ke dalam Bahasa Indonesia Berbasis Media Komunikasi Elektronik Youtube - Indah Isti Widyatama; Abdul Ngalim; Markhamah Markhamah (Jurnal Penelitian Humaniora, 2021)
This study has two objectives: (1) to identify interference of the English lexicon into Indonesian used on Youtube and (2) to identify the imple-mentation of the development of Youtube-based English lexicon interfer-ence teaching material into Indonesian. This research is a qualitative description which involve data in the form of video from Youtube. The collection techniques are using listening methods and collecting record-ings, taking notes, observation and focus group discussions which in-volve studens. The data analysis technique uses translational equivalent method and the aggregate method. The results of this study show that there are six forms of interference of the English lexicon into the Indone-sian language. (a) 39 nouns, (b) 6 verbs, (c) 3 pronouns, (d) 1 conjunc-tion, (e) 3 adverbs, and (f) 8 adjectives. This finding is useful in the im-plementation of sociolinguistic learning with lexicon interference mate-rial from English into Indonesian based on the standard set by the Minis-try of Education.